Mediation as an alternative method of dispute resolution: International and national practices in legal regulation - M. Deineha (Law. Human. Environment)
The relevance of the subject under study is conditioned upon the fact that the strengthening of Ukraine’s European integration requires the introduction of new, alternative methods of dispute resolution in national legislation and practice, among which mediation occupies a prominent place, the functioning of which has successfully proven itself in developed European countries. The purpose of this study was to figure out the current state of development of legal support for mediation in Ukraine, to outline prospects for improving legal regulation, considering International and European standards of mediation. The study used a system of general scientific methods of cognition (dialectical method, formal logical method, method of analysis and synthesis), as well as special legal methods (comparative legal method, formal legal method). The authors analysed the international and national practices of legal regulation of mediation in the system of alternative dispute resolution methods. Doctrinal and legislative approaches to the interpretation of the mediation were described, its main advantages in the system of alternative dispute resolution methods were found, types of mediation were outlined, and the content of the main international, European, and Ukrainian regulations governing relations in mediation were covered. It was found that mediation occupies a priority position in the international practices of conflict resolution, since it is much more effective than judicial and administrative forms of protection of rights and legitimate interests. It was proved that the attractiveness of mediation lies precisely in the simplicity and convenience of the procedure, a calm atmosphere of dialogue and the obligation to consider the opinions of all involved parties. It was found that this legal institution is based on voluntariness, confidentiality, impartiality, and neutrality, the possibility for participants to make their own decisions, and the presence of independent support of each participant from the mediator. It was noted that, despite the national legal framework for mediation developed in Ukraine, the outlined sphere of public relations requires improvement of the relevant legal mechanism and the institutional basis for its implementation. The results obtained can be used in further studies, as well as in the development of new and changing the existing regulations that determine the legal basis of mediation in the practice of implementing relevant legislation.